Burocracia de médio escalão em contexto de crise: um estudo de caso sobre os efeitos da pandemia de Covid-19 nas políticas assistenciais de Belo Horizonte - Guimarães, Flávia Alves (2022)
This study proposes to verify if the pandemic of COVID-19 has caused changes in the necessary capabilities for the execution of the social assistance policies developed by the Secretaria Municipal de Assistência Social, Segurança Alimentar e Cidadania de Belo Horizonte (SMASAC), in 2020, and if these changes affected the performance of mid-level bureaucracy of the secretary. This is an exploratory and qualitative research study, which adopted the case study as its research strategy. The case study was operationalized in several stages: delimitation of the case-unit, theoretical review, data collection, analysis and interpretation of the findings. A literature research was conducted that privileged three theoretical dimensions: crisis management, state capacity, and mid-level bureaucracy. The year of 2019 was considered as a reference of the pre-pandemic period, and the year of 2020, for the pandemic period. To understand how SMASAC acted in both periods, a documentary research was conducted, which was based on access to legislation, technical notes, reports on the measures adopted by the municipal administration, management balance sheets, and budget statements. For the purposes of this study, the municipal policies of social assistance, food and nutritional security, and human rights were the social assistance policies evaluated. State capacity was considered as the set of capabilities required to carry out public policies and implement official objectives, privileging the administrative dimension of the concept. Considering the mid-level bureaucrats part of the arrangement of the capacity necessary to execute public policies, through semi-structured interviews and the application of a questionnaire, the perception of these actors from the intraorganizational dimension of public administration about the changes brought by the crisis was captured. By comparing the data obtained about the two periods considered in the research, it was possible to observe the effects of the public health emergency situation on the assistance policies that were being developed by SMASAC. If the objectives until 2019 were focused on the improvement of management and the expansion of priority offerings, in 2020, the guarantee of social protection and emergency food provision became the focus of management. The change in the agency's objectives had effects on the necessary capacities for the execution of public policies. As for the effects of the pandemic on the performance of the mid-level bureaucracy, based on the perceptions of the managers, it was noted that the crisis affected the work regime, the decision-making processes, the interactions with other actors, and the skills required to perform the functions of these government actors. It is expected that the considerations presented in this dissertation contribute to the production of knowledge about the effects of the pandemic of COVID-19 in public administration, especially in social assistance policies; that from the reading of this crisis context it has also been possible to uncover aspects of the performance of mid-level bureaucrats and, consequently, of the back office of municipal management in atypical situations.